The Effect of Service Quality on Indihome Customer Satisfaction in the Kuta Alam Region of Banda Aceh - Natalia, Desy Uli (Business and Investment Review, 2023)
We live in an era where the use of technology is becoming more and more booming. Technology offers advantages in the field of knowledge and provides users with convenient access to scientific information. In addition to non-profit technology, user growth and informatics, a new innovation is Mancula's fixed broadband high-speed Internet network. IE PT. Telecom Nikasi Indonesia Tbk, one of the providers of fixed-line broadband services, has launched a new product called Indihome. The purpose of this study is to determine consumer reaction to service quality and customer satisfaction in Indyhome Antapani Bandung area. As a method, a quantitative research method in the form of causal relationship research is used. Sampling was performed using probability sampling, a simple random sampling, with a maximum total of 75 respondents. Descriptive analysis and simple linear resistance analysis were then used for data analysis. Based on the results of hypothesis testing, Indihome partially has a significant impact on customer satisfaction, with the magnitude of the impact being 23.91%, while the remaining 76.09% are due to other factors i.e. brand image, location , price, etc. cause. Abstrak Penggunaan teknologi saat ini semakin berkembang pesat. Teknologi menawarkan keuntungan dalam dunia informasi dan juga memudahkan pengguna untuk mengakses informasi ilmiah. Dengan bertambahnya pengguna telekomunikasi dan teknologi informasi, muncul inovasi baru yaitu internet fixed broadband berkecepatan tinggi. Perusahaan penyedia layanan fixed broadband yaitu PT.Telekomunikasi Indonesia Tbk meluncurkan produk baru bernama Indihome. Tujuan dari penelitian ini adalah untuk mengetahui respon konsumen terhadap kualitas pelayanan dan kepuasan pelanggan Indihome di wilayah Kuta Alam Banda Aceh. Metode yang digunakan adalah metode kuantitatif dengan jenis penelitian berupa penelitian kausal. Pengambilan sampel dilakukan dengan menggunakan metode simple random sampling dengan jumlah 75 responden. Kemudian, analisis deskriptif dan analisis regresi linier sederhana digunakan untuk analisis data. Berdasarkan hasil uji hipotesis secara parsial kualitas pelayanan Indihome berpengaruh signifikan terhadap kepuasan pelanggan dengan besaran sebesar 23,91%, sedangkan sisanya sebesar 76,09% dipengaruhi oleh faktor lain seperti brand image, lokasi, harga atau faktor lainnya. Kata Kunci: Kualitas Pelayanan, Kepuasan Pelanggan, Teknologi